Assessment of modulated cytostatic drug resistance by automated γH2AX analysis. (2nd April 2015) - Reddig, Annika; Lorenz, Sebastian; Hiemann, Rico; Guttek, Karina; Hartig, Roland; Heiserich, Lisa; Eberle, Caroline; Peters, Vanessa; Schierack, Peter; Sack, Ulrich; Roggenbuck, Dirk; Reinhold, Dirk
Abstract The efficacy of many chemotherapeutic agents relies on the preferential destruction of rapidly dividing cancer cells by inducing various kinds of DNA damage. The most deleterious type of DNA lesions are DNA double‐strand breaks (DSB), which can be detected by immunofluorescence staining of phosphorylated histone protein H2AX (γH2AX). Furthermore, γH2AX has been suggested as clinical pharmacodynamic biomarker in chemotherapeutic cancer treatment. A great challenge in treating neoplastic diseases is the varying response behavior among cancer patients. Thus, intrinsic or drug‐induced overexpression of efflux pumps often leads to multiple drug resistance (MDR) and treatment failure. In particular, inter‐individual differences in expression levels of efflux pumps, such as the permeability glycoprotein (P‐gp), were shown to correlate with cancer progression. Several efficient cytostatic drugs, including the DSB‐inducing agent etoposide (ETP) are known P‐gp substrates. In this respect, modulation of MDR by P‐gp inhibitors, like the immunosuppressives cyclosporine A (CsA) and rapamycin (Rapa) have been described. Here, we investigated the application of γH2AX focus assay to monitor the impact of CsA and Rapa on ETP‐induced cytotoxicity in human peripheral blood mononuclear cells. Evaluation of γH2AX foci was performed by the automated fluorescence microscopy and interpretation system AKLIDES. Compared to ETP treatment alone, our results revealed a significant rise in γH2AX focus number and percentage of DSB‐positive cells after cells have been treated with ETP in the presence of either CsA or Rapa. In contrast, DSB levels of cells incubated with CsA or Rapa alone were comparable to focus number of untreated cells. Our results successfully demonstrated how automated γH2AX analysis can be used as fast and reliable approach to monitor drug resistance and the impact of MDR modulators during treatment with DSB‐inducing cytostatics. © 2015 International Society for Advancement of Cytometry